Orthodontic aligners: between passion and science - Mendes Ribeiro, Suelly Maria; Aragón, Mônica Lídia Santos de Castro; Espinosa, Daybelis del Socorro González; Shibasaki, Wendel Minoro Muniz [UNESP]; Normando, David (FapUNIFESP (SciELO), 2023)
Introduction: The benefits and safety of using orthodontic aligners have been reported more by clinical experience and expert opinion than by scientific evidence. Another important aspect is that aligners are constantly evolving. It is important to obtain evidence that allows for new updates in manufacturing technology, in the development of new movement planning protocols, in the incorporation and design of attachments, and in the aid of skeletal anchorage. Methods: Evidence retrieved from six electronic databases (CINAHL, MEDLINE, EMBASE, Psych Info, the Cochrane Library and the Joanna Briggs Library) is presented by means of questions and answers. Conclusions: There is evidence that the aligners presented different levels of difficulty in performing each type of movement, with rotational and vertical movements being the most difficult to perform. Regarding perception of pain due to tooth movement, it seems to have less impact at the beginning of treatment; but dealing with more phonoarticulatory changes seems to require more treatment time in more complex cases. Aligners do not prevent the occurrence of root resorption, although the incidence and severity of resorption may be reduced, making oral hygiene easier and accepting the risk of white spots, caries and periodontal disease. Given the conflicting evidence, the release of bisphenol-A from the aligner cannot be denied. Solutions must be found to reduce the environmental impact of aligners disposal. There is an urgent need for well-designed randomized controlled trials.
Keywords: Aesthetics; Biocompatibility; Biomechanics; Malocclusion; Orthodontic aligners; Quality of life; Removable orthodontic appliance; Root resorption; Sustainability; Tooth movement